Methodology for work measurement of the human factor in industry. (1st January 2014) - Tajini, Reda; Elhaq, Saâd Lissane
The current industrial context, characterised by an increasingly strong competition, is forcing companies to improve the performances of their production system, to respond to customer demand that is unpredictable and unstable. In this regard, the automotive wiring industry in Morocco is characterised by high employability, hence the need to develop methods of work measurement. This approach will assess, analyse and optimise all activities of the production system taking into account the human factor that remains unpredictable and represents the core of this business. In this context, this paper presents a methodology for work measuring of each position of a production line in the wiring industry, to improve its productivity and efficiency.